Designing Scoring Rubrics for Assessing English Conversation Teachers’Performance - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
Studies on language tests and assessment have been discussed for years. Most of them deal with how to assess students’ performance, or how to write a good test. However, we lack investigations onteachers’ performance assessment, particularly on  English Conversation teachers’.One of the most common assessment tools used to evaluate teachers performance is Communicative Orientation of Language Teaching (COLT)—an observation scheme deployedin a classroom; nevertheless, it is not specifically devised for conversation classes. We also have other kinds of teacher evaluation rubrics, yet they cover dimensions of how teachers perform in class in general. Thus, it is imperative to design  scoring rubrics for assessing English conversation teachers’ performance.This paper discusses  preliminary research on scoring rubrics designed to assess English conversation teachers’ performance. It includes what dimensions should be assessed in the scale and the score for each dimension. It wouldbe like a band scale used to assess students’ oral communication skills. This research deployed qualitative research as the data analysed were  the non-numerical ones. The results of the study showed that it was not an easy assignment to design scoring rubrics to assess conversation teachers’ performance as teachers’ response to the designed scoring rubrics varied greatly. Keywords: Scoring rubrics, English conversation classes, and teachers’ performance